Energy taxation, subsidy removal and poverty in Mexico. (23rd June 2021) - Labeaga, José M.; Labandeira, Xavier; López-Otero, Xiral
Abstract: Equity and efficiency are crucial issues behind any tax reform, but they are particularly relevant in countries with high inequality and large shares of poverty. This paper provides a comprehensive socio-economic empirical assessment of Mexico's proposed (and partially implemented) tax reforms in the energy domain, and of a hypothetical partial removal of existing electricity subsidies. Using a rich household income and expenditure survey within the context of a demand system adjustment of non-durable goods, the article provides the public-revenue, environmental and distributional impacts from the simulation of different combinations of energy taxation, subsidy-removal and distributive offsets. The paper also provides detailed ex-ante evidence on the effects of compensatory devices that may contribute to the successful implementation of energy reform packages and significant poverty alleviation in Mexico.